Analisis Pengaruh Kecerdasan Emosional, Kecerdasan Spiritual, dan Love of Money Terhadap Persepsi Etis Mahasiswa Akuntansi Mengenai Etika profesi Akuntan (Studi Kasus Pada Universitas Swasta Jurusan Akuntansi Kota Semarang) - Laila Mangiskar (Universitas Muhammadiyah Semarang, 2019)
Abstract____________________________________________________________This research was conducted to determine: (1) the effect of emotional intelligence on the ethical perceptions of accounting students regarding the professional ethics of accountants; (2) The Effect of Spiritual Intelligence on the Ethical Perceptions of Accounting Students Regarding Accountants' Professional Ethics; (3) The Effect of Love of Money on the Ethical Perceptions of Accounting Students Regarding Accountants' Professional Ethics; (4) The simultaneous influence of Emotional Intelligence, Spiritual Intelligence and Love of Miney on Accounting Students 'Ethical Perceptions of Accountants' Professional Ethics. The population in this study were accounting students at the University of Semarang, Sultan Agung Islamic University, Stikubank University, Soegijapranata Catholic University and Dian Nuswantoro University. The sample in this study were 95 respondents. The prerequisite test includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The data analysis technique used to test the hypothesis is multiple linear regression analysis. The results showed that partially Emotional Intelligence had a positive and significant effect on the Ethical Perceptions of Accounting Students Regarding the Professional Ethics of Accountants as evidenced by the regression coefficient value showing the direction of the positive relationship of 0.085 and the sig value of 0.000 <0.050; Spiritual Intelligence has a positive and significant effect on the Ethical Perceptions of Accounting Students Regarding Accountants' Professional Ethics as evidenced by the regression coefficient which shows the direction of the positive relationship of 0.100 and the sig value of 0.000 <0.050; Love of Money has a negative and significant effect on the Ethical Perceptions of Accounting Students Regarding Accountants' Professional Ethics as evidenced by the regression coefficient value which shows the direction of the negative relationship of -0.030 and the sig value of 0.004 <0.050; Emotional Intelligence, Spiritual Intelligence and Love of Money simultaneously influence the Ethical Perceptions of Accounting Students Regarding Accountant Professional Ethics as evidenced by the value of Fcount is greater than Ftable, namely 14.243> 2.70 and a significance value of 0.000 <0.050.